CHARACTERISTICS OF EATING PATTERN AND FOOD VARIETY IN TODDLER WITH NUTRITION PROBLEMS - Yolanda, Henny; Karjono, M.; Supinganto, Agus; Mulianingsih, Misroh; Haris, Abdul; Hayana (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Developmental disorders such as malnutrition in a child's early years can have a detrimental impact on all developmental domains, as these years contain the most rapid changes in brain development. Behavior in implementing balanced nutrition by restraining consumption of vegetables, fish and fruit by maximizing local food, or local food with regional specialties according to local conditions. Objective: The aim of this study was to determine the characteristics of eating pattern and food variety in toddler with nutritional problems. Methods: This study used descriptive analysis design with cross-sectional approach. This study was conducted on 1-31 August 2022 with 54 participants of mothers and children (12-48 months). The instruments in this study used 24-hour food recall instrument. The analysis of this study used descriptive analysis. Result: The characteristic of complementary feeding of children with nutrition problems was good eating patterns and 4 varieties of food every time they eat. Conclusion: Food variety in children with nutritional problems was good eating patterns with an average consumption of 4 types of food at each meal.